2014
DOI: 10.3892/br.2014.273
|View full text |Cite
|
Sign up to set email alerts
|

Calcium butyrate: Anti-inflammatory effect on experimental colitis in rats and antitumor properties

Abstract: Butyric acid is a physiological component of the colonic environment that possesses anti-inflammatory and antitumor properties, among others. However, little is known regarding its effects following direct application on the colonic surface. This study was conducted to investigate the topical anti-inflammatory effect of calcium butyrate in chemically-induced colitis in rats and to evaluate its antitumor properties and. The anti-inflammatory activity of calcium butyrate was evaluated in dinitrobenzene sulfonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Butyrate is anti-inflammatory (Van Immerseel et al, 2010 ; Celasco et al, 2014 ), and some of the identified cecal bacteria were assigned to known butyrate-producing genera, such as Faecalibacterium, Subdoligranulum , and Butyricicoccus (Louis and Flint, 2009 ). Faecalibacterium was more predominant in the cecal digesta of reused-litter chickens, while Subdoligranulum showed the opposite trend at both ages (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate is anti-inflammatory (Van Immerseel et al, 2010 ; Celasco et al, 2014 ), and some of the identified cecal bacteria were assigned to known butyrate-producing genera, such as Faecalibacterium, Subdoligranulum , and Butyricicoccus (Louis and Flint, 2009 ). Faecalibacterium was more predominant in the cecal digesta of reused-litter chickens, while Subdoligranulum showed the opposite trend at both ages (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lipid components of dairy products, including butyric acid and CLA, may protect against tumorigenesis ( 40 ) . Butyric acid is a major metabolite in colonic lumen that possesses anti-inflammatory and anti-tumour properties ( 43 ) . Milk lipid is the main dietary source of CLA.…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate acts as an acid-forming agent that has anti-inflammatory and anticarcinogenic properties [2,17]. This additive acts as the main source of energy for colonocytes and A c c e p t e d A r t i c l e enterocytes.…”
Section: Incidence Of Diarrheamentioning
confidence: 99%
“…Thus, alternative additives to performance-enhancing antibiotics, such as organic acids and "plant extracts" should be investigated. Butyrate is a salt of a short-chain fatty acid produced in the colon by the gastrointestinal microbiota [2]. This fatty acid has antimicrobial properties, stimulates cell epithelial proliferation, acts as an anti-inflammatory agent and assists in intestinal motility [2,3].…”
Section: Introductionmentioning
confidence: 99%